EXPRESS METHOD FOR CALCULATING GROSS MARGIN IN E-COMMERCE: A PRACTICAL APPROACH - Viktoriia Zalizniuk; Oleh Nozhovnik (Baltic Journal of Economic Studies)
The purpose of this study is to present a streamlined approach to calculating the gross margin of online stores, with a particular focus on addressing the specific requirements of small and medium-sized enterprises (SMEs) within the e-commerce sector. This research presents a comparative analysis between the traditional method of gross margin calculation and an express approach that utilises the average order value (AOV) as a central metric. The objective of this study is to evaluate the efficiency and accuracy of the express method, particularly in the context of SMEs that may lack the resources required for more complex financial analyses. Methodology. A quantitative research design is employed, utilising data from three online retailers specialising in the sale of home textiles and linens produced by an in-house sewing studio. The shops in question operate on a number of e-commerce platforms, including Rozetka, Etsy, eBay, and Prom.ua. The study encompasses a period of eight months, during which sales data was collected and analysed in order to evaluate the efficacy of both manual and express methods of gross margin calculation. The express method incorporates statistical analysis, including z-scores and normal distribution, to provide a probabilistic framework for the assessment of the likelihood of achieving target gross margin ranges under different pricing scenarios. Results. The findings of the study indicate that the express method suggests a probability of achieving a gross margin within the 25-30% range, with a 38.11% likelihood. A case study utilising tulle curtains demonstrates the practical application of the aforementioned method. Following the implementation of a 20% discount, the gross margin experienced a notable decline, from 33.9% to 17.36%. Furthermore, the results of the z-score analysis indicate that the probability of exceeding a 30% gross margin is 27.43%, while the likelihood of the margin falling below 25% is 34.46%. This analysis underscores the inherent risks associated with offering discounts and illustrates the potential for significant fluctuations in profitability contingent upon price adjustments. Practical implications. The express method offers invaluable insights that can inform decision-making in a range of retail contexts. To illustrate, an online fashion retailer may utilise the method to evaluate the influence of price increases on gross margin during seasonal promotions. Similarly, a home goods store could employ the method to ascertain the impact of a flash sale discount on profitability, thereby facilitating the balancing of margins with sales volume. Value / Originality. The express method introduces a novel approach by integrating AOV and probabilistic analysis into gross margin calculation. This offers a dynamic framework that accounts for variability in discounts and sales, which is a significant advantage over traditional methods that rely on fixed margin targets or historical averages.